ANALISIS PENGARUH PROFITABILITAS, UKURAN PERUSAHAAN DAN UKURAN KANTOR AKUNTAN PUBLIK (KAP) TERHADAP AUDIT DELAY PADA PERUSAHAAN PERTAMBANGAN PERIODE 2010 – 2014 - Apriani, Sarah; Rahmanto, Basuki Toto (Jurnal Riset Manajemen dan Bisnis (JRMB) Fakultas Ekonomi UNIAT, 2017)
Firms listed on the Stock Exchange shall publish the audited financial statements to OJK, d/h Bapepam – LK results no later than 4 months or 120 days since the publication of the annual report. This study was conducted to examine the effect of profitability, company size and Office of Public Accountants (KAP) to Audit Delay in mining companies, for coal, rocks, metal, and minerals, with oil and gas sectors in Indonesia Stock Exchange 2010-2014. Sample This study covers 13 companies. Sampling method using purposive sampling. This study uses secondary data were analyzed using multiple linear regression. The results of the analysis concludes that a effect on the profitability of the audit delay, company size and Office of Public Accountants (KAP) has no effect on audit delay due to the significant value of the variable that is more than 0,05. Keywords: Profitability, Company Size, Public Accountant Office, Audit Delay